Analysis of The Traditional Birth Attendants Knowledge Level in Assisting Delivery According to Health Standards And Its Influencing Factors - Patresia J Maiseka (Asian Journal of Social and Humanities, 2023)
This study purposed to determine the level of knowledge of TBAs in assisting deliveries according to health standards, and its correlation to personal factors such as age, education, family history, and history of training in Gorom Island, East Seram, Maluku. 25 TBAs in Gorom Island agreed to participate in a survey by filling out questionnaires concerning their personal data and knowledge of delivery assistance according to health standards. The questions include the stages of labor management, the sterility of techniques and tools used, and the emergency responses. The data were then examined by analytical descriptive study with a cross-sectional approach. This study found Only 20% of TBAs had a good level of knowledge to assist delivery according to health standards. The history of training is correlated with the level of knowledge. Approximately 80% of TBAs with good knowledge had attended delivery training by health workers. They understood the management, limits, and responses to emergencies in labor. In contrast, most TBAs with moderate (44%) and poor (36%) knowledge with no training history, still had a traditional understanding of labor equipment and methods used. The skills and knowledge of TBAs in assisting deliveries according to health standards are highly dependent on education and guidance from health workers.